Analisis Pengaruh Financial Leverage, Debt of Equity Ratio dan Current Ratio Terhadap Earning Per Share pada Industri Sektor Migas yang Listing di BEI - B51110039, FAUZI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Purpose of this study was to examine and analyze the effect of financial leverage, debt of equity ratio and current ratio to earnings per share in the oil and gas industry are listed on the Stock Exchange Type of this research is quantitative research. The sample used by 8 companies. Data collection methods is the study documentation. Data analysis using multiple linear regression Results of this study showed that simultaneous financial leverage as measured by long-term debt to equity ratio, current ratio as measured by the natural log of the net state debt and equity ratio significantly affect earnings per share. Partially current ratio significant effect on earnings per share, while financial leverage and debt ratio ofequity no significant effect on earnings per share The value of coefficient of determination (R2) of 0.248 or 24.8%, which means the ability of the influence of all the variables financial leverage, debt of equity ratio and current ratio to earnings per share is 24.8% while the rest influenced by other factors not included in the study this. Keywords : financial leverage (long termdebt to equity ratio ) , debt of equity ratio and current ratio (log net natural state) and earnings per share